2012
DOI: 10.1152/ajpheart.01170.2011
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of short periods of rapid atrial pacing on left and right atrial mechanical function

Abstract: Current techniques to describe atrial function are limited by their load dependency and hence do not accurately reflect intrinsic mechanical properties. To assess the impact of atrial fibrillation on atrial function, combined pressure-volume relationships (PVR) measured by conductance catheters were used to evaluate the right (RA) and left (LA) atrium in 12 isoflurane-anesthetized pigs. Biatrial PVR were recorded over a wide range of volumes during transient caval occlusion at baseline sinus rhythm (SR), after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Through a purse-string suture in the ascending aorta, a 5F PV conductance catheter (Millar SPR-766; Millar Instruments, Inc, Houston, Tex) was introduced and positioned along the long axis of the LV, with the tip of the catheter resting in the LVapex. 3 The pericardium was kept intact in both the control and paced animals. A second conductance catheter was inserted through a small pericardial incision into the LA through a purse-string suture at the base of the appendage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through a purse-string suture in the ascending aorta, a 5F PV conductance catheter (Millar SPR-766; Millar Instruments, Inc, Houston, Tex) was introduced and positioned along the long axis of the LV, with the tip of the catheter resting in the LVapex. 3 The pericardium was kept intact in both the control and paced animals. A second conductance catheter was inserted through a small pericardial incision into the LA through a purse-string suture at the base of the appendage.…”
Section: Methodsmentioning
confidence: 99%
“…The impact of prolonged AF on left atrial (LA) and left ventricular (LV) function has been incompletely characterized. Although there have been reports on the effect of paroxysmal atrial fibrillation (PAF) on LA and LV function by echocardiography 2 and reports on the effect of acute AF on LA and LV function by conductance catheter in an animal model, 3 there are few reports describing the influence of AF on LA and LV function and volume, and the severity of fibrosis induced by a defined period of AF.…”
mentioning
confidence: 99%
“…LA pressure and LA volume or strain were synchronized to generate LA pressure-volume or pressure-strain loops. As previously demonstrated, the LA pressure-volume relationship typically represents a figure-of-eight pattern, with the two loops consisting of A-and V-loops (30). The A-loop represents active atrial contraction and relaxation, and the V-loop represents passive atrial reservoir filling and emptying.…”
Section: Discussionmentioning
confidence: 91%
“…The area inside of each loop represented external work. Other studies invasively measured the LA pressurevolume loops using a conductance catheter; however, it is methodologically challenging to evaluate the LA external work with this catheter (10,30).…”
mentioning
confidence: 99%
“…Animal studies on the effects of RAP on atrial remodeling demonstrated different impacts of pacing on right and left atrial functions with heterogeneity of sympathetic innervation predisposing to sustained AF. Weimar et al investigated the hemodynamic impact of AF on RA and LA during RAP and after restoration of sinus rhythm in an acute pig model by using combined pressure‐volume relationships and demonstrated a differential impact on RA and LA function of short periods of RAP, which was sustained for 1 hour after conversion to SR. Berenfeld et al demonstrated disorganized RA conduction after periodic high‐frequency pacing at the RA in a sheep model. In another RAP‐induced AF in dogs, Jayachandran et al, reported that RAP‐induced AF results in both autonomic and electrophysiological remodeling of the atria.…”
Section: Discussionmentioning
confidence: 99%